Nii Ndahlohke: Boys' and Girls' Work at Mount Elgin Industrial School, 1890-1915 - McCallum, Mary Jane Logan (Friesen Press, 2022)
This book takes its title from the phrase for “I work” in Lunaape, the traditional language of Munsee Delaware people, and was inspired by the work of the Munsee Delaware Language and History Group. Written for the descendants and communities of children who attended Mount Elgin and intended as a resource for all Canadians, Nii Ndahlohke tells the story of student life at Mount Elgin Industrial School between 1890 and 1915. Like the school itself, Nii Ndahlohke is structured in two sections. The first focuses on boys’ work, including maintenance and farm labour, the second on girls’ work, such as cooking, cleaning, and laundry. In Nii Ndahlohke readers will find a valuable piece of local, Indigenous, and Canadian history that depicts the nature of “education” provided at Canada’s Indian residential schools and the exploitation of children’s labour in order to keep school operating costs down. This history honours the students of Mount Elgin even as it reveals the injustice of Indian policy, segregated schooling, and racism in Canada. –Publisher's description
https://www.niindahlohke.ca/